Two Opisthographs and Scribal Practices in the Ancient Near Eastern World: Thoughts on Use and Reuse - Ayhan Aksu (Papers from the Institute of Archaeology, 2022)
Recent scholarship has developed an increasing interest in the materiality of ancient manuscripts. Opisthographs, manuscripts that contain writing on both sides, are of special interest in this regard. This short study focuses on two papyrus opisthographs, originating from two different collections: the Oxyrhynchus Papyri and the Dead Sea Scrolls. These manuscripts each bear different compositions on the front side (the recto) and on the back side (the verso). The Greek Papyrus Oxyrhynchus 654 (dated to the third century CE) contains on its recto an unpublished survey-list of pieces of land. On the verso we find one of the three copies of the Greek version of the Gospel of Thomas. The Dead Sea Scroll 4Q509, Festival Prayers, is the recto of a Hebrew papyrus that bears copies of two compositions on its verso: the War Scroll (4Q496) and Words of the Luminaries (4Q506). These texts were dated to the first century BCE and the middle of the first century CE. By contextualizing these two manuscripts, I aim to explore the nature of opisthographs as a scribal phenomenon across different cultures in the region. This comparative research will be conducted by considering the materiality of these manuscripts from the perspective of both codicology and palaeography. Subsequently, I will investigate the intertextual relationships between the compositions on both sides of the manuscripts and address related issues such as the ‘useful life’ of these manuscripts and the possibility of personal copies.